2017
DOI: 10.1186/s12951-017-0310-5
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials modulate stem cell differentiation: biological interaction and underlying mechanisms

Abstract: Stem cells are unspecialized cells that have the potential for self-renewal and differentiation into more specialized cell types. The chemical and physical properties of surrounding microenvironment contribute to the growth and differentiation of stem cells and consequently play crucial roles in the regulation of stem cells’ fate. Nanomaterials hold great promise in biological and biomedical fields owing to their unique properties, such as controllable particle size, facile synthesis, large surface-to-volume r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 146 publications
(186 reference statements)
0
76
0
Order By: Relevance
“…Tissue engineering is a multidisciplinary approach that has revolutionized regenerative medicine over the years. This research area has been enriched by the increasing progress of nanotechnology allowing the development of new methodologies to obtain different nanostructures, the understanding of their properties and the interactions between the nanomaterials and other types of constituents (Solanki, Kim, & Lee, ; Van Rijt & Habibovic, ; Wei, Li, & Le, ).…”
Section: Introductionmentioning
confidence: 99%
“…Tissue engineering is a multidisciplinary approach that has revolutionized regenerative medicine over the years. This research area has been enriched by the increasing progress of nanotechnology allowing the development of new methodologies to obtain different nanostructures, the understanding of their properties and the interactions between the nanomaterials and other types of constituents (Solanki, Kim, & Lee, ; Van Rijt & Habibovic, ; Wei, Li, & Le, ).…”
Section: Introductionmentioning
confidence: 99%
“…Given that a good surface hydrophilicity generally promotes cell adhesion and spreading 21,24 , in order to further characterize the substrate surface properties, we evaluated water wettability by performing water contact angle measurements ( Fig. 1f).…”
Section: Resultsmentioning
confidence: 99%
“…This long time period, for which the addition of NPs does not consist with toxic response, grants an extension provided either to their in vivo time of action or the in vitro induced differentiation towards the regeneration of damaged areas of the body. Several researchers have reported that using nanomaterials as 2D cell culture substrate could effectively promote the differentiation of stem cells into specific lineages, and the stiffness, surface chemistry, alignment and several other parameters of the cell culture substrate (matrix) may work together to influence the fate of stem cells [32]. Our findings provide strong evidence that the resulting nanocomposite PCL thin films not only passively interact with cells, but also serve as mechanical stimuli that trigger a series of biological alterations and modulate cell behaviors.…”
Section: Discussionmentioning
confidence: 99%